OsDRE2 contributes to chitin-triggered response through its interaction with OsRLCK185. Issue 2 (1st February 2019) - Yamaguchi, Koji; Yoshimura, Yuya; Nakagawa, Shinya; Mezaki, Hirokazu; Yoshimura, Satomi; Kawasaki, Tsutomu
ABSTRACT: The rice receptor-like cytoplasmic kinase 185 (OsRLCK185) interacts with the chitin receptor complex OsCERK1/CEBiP and positively regulates chitin-induced immune responses including MAP kinase activation, ROS production and defense gene expression. To elucidate the regulatory mechanisms of OsRLCK185-mediated immunity, we searched for interactors of OsRLCK185. OsDRE2a, rice homologs of the yeast Dre2 protein, were identified as novel interactors of OsRLCK185. OsDRE2a interacted with OsRLCK185 at plasma membrane. The conserved cysteine residues in CIAPIN1 domain of OsDRE2a were essential for tight interaction of OsRLCK185. OsDRE2a was phosphorylated by OsRLCK185. The expression of OsDRE2a and OsDRE2b was induced after chitin treatment. Reduction of OsDRE2a and OsDRE2b mRNA levels by RNA interference resulted in the decreased chitin-induced ROS production. Thus, it is likely that OsDRE2 regulates OsRLCK185-mediated immune responses. Graphical abstract: : OsDRE2 interacts with OsRLCK185 at plasma membrane and is phosphorylated by OsRLCK185. Silencing of OsDRE2 causes the reduction of chitin-induced ROS production.